Studies on ancient metalworking techniques: preliminary report (Research Announcements "Heritage BG", 2024)
This preliminary report focuses on two techniques of jewellery production. The first technique is granulation, and the second is filigree. We know both techniques from different gold jewellery from ancient Thrace. The aim of this study is to gain more knowledge about the use of these techniques, the production steps, and possibly, the technological knowledge of the fine working metalworker. With the help of experimental archaeology, both techniques are examined to draw conclusions about their application, the tools used and the technological knowledge of the craftsmen. References:Ginev, G. (1983). Sakrovishteto ot Kralevo. Izdatelstvo Balgarski hudozhnik. Sofia.Kitov, G. (1994). Dolinata na tsarete v Kazanlashkata kotlovina. - Anali 2 / 3, 46-76.Torbov, N. (2015). Mogilanskata mogila vav Vratsa. Katalog Vratsa.Filow, B. (1934). Die Grabhügelnekropole bei Duvanlij in Südbulgarien. Sofia.Filow, B., & Welkow, I. (1930). Grabhügelfunde aus Duvanlii in Süd-bulgarien. Sonderdruck aus dem Jahrbuch des deutschen Archäologischen Institutes 45, 3/4, Berlin.Hachmann, R. (1983). Frühe Phöniker im Libanon. 20Jahre deutsche Ausgrabungen in Kamid el Loz. Ausstellungskatalog Saarbrücken. Mainz.Moesta, H. (1983). Erze und Metalle – ihre Kulturgeschichte im Experiment. Berlin, Heidelberg, New York.Nestler, G., & Formigli, E. (1993). Etruskische Granulation. Eine antike Goldschmiedetechnik. Siena.Ogden, J. (1991). Classical gold wire: Some aspects of its manufacture and use. – Jewellery Studies 5, 95-105.Özşen, I. (2021). Drahtziehen und die dazugehörigen Werkzeuge im Altertum. PhD Dissertation, Kultur-, Sozial- und Bildungswissenschaftliche Fakultät. Berlin. https://edoc.hu-berlin.de/handle/18452/26503 (Accessed 09.04.2023).Roth, H. (1986). Kunst und Handwerk im frühen Mittelalter. Archäologische Zeugnisse von Childerich I. bis zu Karl dem Großen. Stuttgart.Tolstikow, W., & Trejster, M. (1996). Der Schatz aus Troja: Schliemann und der Mythos des Priamosgoldes. Ausstellungskatalog Moskau 1996/97. Stuttgart, Zürich.Williams, D., & Ogden, J. (1994). Greek Gold. Jewellery of the classical world. Verona.Wolters, J. (1983). Die Granulation. Geschichte und Technik einer alten Goldschmiedekunst. München.Wolters, J. (1987). Filigran. In: Reallexikon der deutschen Kunstgeschichte. Band 8 Fensterrose – Firnis. München, 1062 – 1183.
Keywords: craftmanship; granulation; filigree